Coincidence Point and Common Fixed Point Results in Cone Metric Spaces Under \(c\)-Distance - Dubey, Anil Kumar; Kasar, Madhubala; Dubey, R. P. (Communications in Mathematics and Applications, 2020)
In this paper, by using the concept of \(c\)-distance in a cone metric space, we prove some coincidence point and common fixed point results with different type of contractive condition. Our results, extend, generalize and improve the corresponding results of Fadail et al. [17-20].
Keywords: Cone metric spaces; c-distance; Common xed point; Coinci- dence point